2017
DOI: 10.1093/ajh/hpx086
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Adherence Trajectories Among Older Adults in the First Year After Initiation of Therapy

Abstract: There is substantial variation in antihypertensive adherence among older adults. Certain patient characteristics are likely determinants of antihypertensive adherence trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 38 publications
3
58
0
1
Order By: Relevance
“…Spaghetti plots have been mentioned in a previous GBTM study, and we recommend all GBTM studies modeling medication adherence as a continuous variable report these plots in the manuscript or appendix. The moderately adherent group's spaghetti plot—supported by this group's distribution of maximum PPs—suggested that these patients did not have a homogeneous pattern of adherence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spaghetti plots have been mentioned in a previous GBTM study, and we recommend all GBTM studies modeling medication adherence as a continuous variable report these plots in the manuscript or appendix. The moderately adherent group's spaghetti plot—supported by this group's distribution of maximum PPs—suggested that these patients did not have a homogeneous pattern of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we evaluated spaghetti plots for 200 randomly selected patients within each group . A single spaghetti plot “strand” represents the longitudinal adherence for one patient; spaghetti plots help visualize adherence patterns of individual patients within each group to assess how well those individual patterns match the group's average adherence.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various factors influence acceptance and persistence with life-long pharmacotherapy, and its patterns are heterogenous. [20] Detection-to-initiation time interval for anti-hypertensive drug therapy is longer in younger, as compared to older hypertensive individuals. [21] Poor economic status, and poor disease control are strong predictors of discontinuation of pharmacotherapy.…”
Section: Initiation Of Therapy For Hypertension and Diabetes Is Necesmentioning
confidence: 99%